2021
DOI: 10.1007/s00366-021-01442-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-strategy Gaussian Harris hawks optimization for fatigue life of tapered roller bearings

Abstract: Bearing is one of the most fundamental components of rotary machinery, and its fatigue life is a crucial factor in designing. The design optimization of tapered roller bearing (TRB) is a complex design problem because various arrays of designing parameters and functional requirements should be fulfilled. Since there are many design variables and nonlinear constraints, presenting an optimal design of TRBs poses some challenges for metaheuristic algorithms. The Harris hawks optimization (HHO) algorithm is a robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 121 publications
(171 reference statements)
0
7
0
Order By: Relevance
“…The quantum particle-enhanced multiple Harris hawks algorithm proposed by Gölcük et al [26] solved the dynamic optimization problem, and it was designed as a multi-population algorithm, which could further process the possible multiple optimal solutions. The multi-strategy Harris hawks optimization algorithm proposed by Abbasi et al [27] was used to solve the tapered roller bearing design problem, which confirmed the effectiveness of the algorithm under complex and variable constraints. The improved HHO algorithm proposed by Hamza et al [28] was used to optimize the prioritization of software testing, and the experimental results highlighted the high efficiency of the MHHO-TCP technique.…”
Section: Introductionmentioning
confidence: 67%
“…The quantum particle-enhanced multiple Harris hawks algorithm proposed by Gölcük et al [26] solved the dynamic optimization problem, and it was designed as a multi-population algorithm, which could further process the possible multiple optimal solutions. The multi-strategy Harris hawks optimization algorithm proposed by Abbasi et al [27] was used to solve the tapered roller bearing design problem, which confirmed the effectiveness of the algorithm under complex and variable constraints. The improved HHO algorithm proposed by Hamza et al [28] was used to optimize the prioritization of software testing, and the experimental results highlighted the high efficiency of the MHHO-TCP technique.…”
Section: Introductionmentioning
confidence: 67%
“…The quantum particle-enhanced multiple Harris hawks algorithm proposed by Gölcük et al [26] solved the dynamic optimization problem, and it was designed as a multi-population algorithm, which could further process the possible multiple optimal solutions. The multi-strategy Harris hawks optimization algorithm proposed by Abbasi et al [27] was used to solve the tapered roller bearing design problem, which confirmed the effectiveness of the algorithm under complex and variable constraints. The improved HHO algorithm proposed by Hamza et al [28] was used to optimize the prioritization of software testing, and the experimental results highlighted the high efficiency of the MHHO-TCP technique.…”
Section: Introductionmentioning
confidence: 67%
“…In (Peng et al, 2021b), Peng et al proposed a multiple strategy serial framework to improve cuckoo search algorithm to avoid the local optimum due to its original unitary search strategy. In (Abbasi et al, 2021), Abbasi et al introduced a chaotic initialization approach and several updated besiege strategies to improve Harris Hawk optimization (HHO) method for the optimal design of tapered roller bearings. Similarly, in (Li et al, 2021a), Li et al presented to use logarithmic spiral and opposition-based learning and a local search technique to improve the global convergence of HHO.…”
Section: Related Workmentioning
confidence: 99%
“…2011 A hybrid 'bee(s) algorithm' for solving container loading problems (Dereli and Das, 2011) a bee(s) algorithm by hybridizing a heuristic filling procedure 2021 Effects of memory and genetic operators on artificial bee colony algorithm for single container loading problem ( Bayraktar et al, 2021) a memory-integrated ABC algorithm 2021 Multi-strategy serial cuckoo search algorithm for global optimization (Peng et al,2021) Cuckoo search algorithm 2021 Multi-strategy gaussian harris hawks optimization for fatigue life of tapered roller bearings (Abbasi et al,2021) Harris Hawk Optimization 2021 Enhanced harris hawks optimization with multi-strategy for global optimization tasks (Li et al,2021) Harris Hawk Optimization 2021 Multi-strategy co-evolutionary differential evolution for mixed-variable optimization (Peng et al,2021) Co-evolutionary differential evolution Continued on next page Categorization Year Titles Features 2021 Differential evolution algorithm with multi-population cooperation and multi-strategy integration (Li et al,2021) Differential evolution algorithm 2021 An adaptive niching method based on multi-strategy fusion for multimodal optimization (Lu et al,2021) Niching method 2021 Ant colony algorithm with stackelberg game and multi-strategy fusion (Chen et al,2021) Ant colony algorithm…”
Section: Table A1 -Continued From Previous Pagementioning
confidence: 99%